South Africa's foreign policy toward the DRC: from non-intervention to intervention 1998 - 2013 - Gbaya, Dada Mbilisi (My University, 2015)
South Africa’s foreign policy toward the DRC has shifted from no military intervention in1998, to military intervention in 2013. This research aims to analyse South Africa’s reluctance to intervene in 1998, while analysing its engagement in peace talks during the second war (2002-2003) and Pretoria’s military intervention in the DRC third war.. South Africa’s post-apartheid foreign policy is enshrined in African National Congress principles. Therefore, since 1994, South Africa’s leaders have formulated and implemented their foreign policy based upon these principles. One of these principles, namely, the promotion of regional peace and security, directed South Africa’s involvement in the DRC crises. Nonetheless, South Africa’s approach to conflict resolution in the DRC shifted from peaceful resolution of the conflict by means of negotiation, as emphasised in the ANC conference in 1997 in Mafikeng –and repeatedly reaffirmed in its following conferences in 2002 in Stellenbosch, in 2007 in Polokwane and in 2012 in Mangaung–to military intervention in the DRC third war. Although South Africa’s current approach to the DRC third war is not clearly stated, its engagement can be understood from what is stipulated in its White Paper on South African Participation in International Peace Missions, adopted by Parliament in October 1999, which commits the country to supporting initiatives of the United Nations and the Organisation of African Unity, where applicable, aimed at the prevention, management and resolution of international conflicts. Therefore, South Africa’s engagement in peacekeeping as well as in current peace enforcement in the DRC is on a multilateral basis under the auspices of United Nations. At the same time, in some quarters, South Africa’s economic interests in the DRC increased substantially from 2006 to 2013.
A research report submitted to the Graduate School of Humanities and Social Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Arts in International Relations by course work and research University of the Witwatersrand 2/16/201